A tuneable, power efficient and narrow single longitudinal mode fibre ring laser using an inline dual-taper fibre Mach–Zehnder filter - Ahmad, Harith; Dernaika, M.; Kharraz, O.M.; Alimadad, M.; Ibrahim, M.F.; Lim, K.S.; Harun, Sulaiman Wadi (IOP Publishing, 2014)
A tuneable single longitudinal mode fibre ring laser with dual-taper fibre filter is proposed and experimentally demonstrated in this paper. The single longitudinal mode operation, and power limitations for a Mach–Zehnder interferometer filter generated from a single mode fibre, are verified for the first time. Incorporating an in-line taper fibre Mach–Zehnder interferometer filter inside the laser ring cavity causes a spatial mode beating interference, resulting in a passive narrow band filter with the ability to generate stable single longitudinal modes. The single longitudinal mode achieves a side mode suppression ratio of more than 60 dB using low pump power. The tuneability of the fibre laser ranges from 1525 to 1562 nm using a passive band pass filter. A study of the stability and limitation of the single longitudinal mode in the Mach–Zehnder tapered fibre is also presented.